MULTIPROFESSIONAL CARE IN CHRONIC WOUNDS - Roque Garcia, Fernanda; Evelly da Silva Olanda, Débora; Fernandes Filgueiras, Mateus; Thallyta Alexandre de Pontes, Arunna; Carolina Salustino dos Santos, Maria; Claudino do Nascimento, Nathalia; Allyson Gomes Ferreira, Jefferson; Costa Soares Silva, Talita; Santos Sousa, Kallyany (Health and Society, 2022)
Chronic wounds are those that produce greater difficulty in the healing process and tissue repair, and in addition, require longer treatment. Reflective research, based on full readings of several studies, in the year 2022. The main results are humanized care, qualified and multiprofessional listening are highlights that deserve attention in the context of long-term treatment of chronic wounds, due to being through these actions that achieve a holistic view of the individual needs of each patient, having materials and professionals trained to continue the care that needs to happen to promote health to this group.